2021
DOI: 10.1073/pnas.2026411118
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of GluN1 gates glycine site–dependent nonionotropic signaling by NMDAR receptors

Abstract: N-methyl-D-aspartate (NMDA) receptors (NMDARs), a principal subtype of excitatory neurotransmitter receptor, are composed as tetrameric assemblies of two glycine-binding GluN1 subunits and two glutamate-binding GluN2 subunits. NMDARs can signal nonionotropically through binding of glycine alone to its cognate site on GluN1. A consequence of this signaling by glycine is that NMDARs are primed such that subsequent gating, produced by glycine and glutamate, drives receptor internalization. The GluN1 subunit conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…We then assessed whether TAT-SAPIP can increase synaptic NMDAR activity (Figure 2). We administered TAT-SAPIP to hippocampal slices while recording post-synaptic responses at the Schaeffer collateral–CA1 synapses( 17 ). Importantly, we found that TAT-SAPIP had no effect per se on the efficacy of synaptic transmission.…”
Section: Resultsmentioning
confidence: 99%
“…We then assessed whether TAT-SAPIP can increase synaptic NMDAR activity (Figure 2). We administered TAT-SAPIP to hippocampal slices while recording post-synaptic responses at the Schaeffer collateral–CA1 synapses( 17 ). Importantly, we found that TAT-SAPIP had no effect per se on the efficacy of synaptic transmission.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, when the NMDAR co-agonist site is occupied by glycine or D-serine at high concentrations, it primes the NMDAR for endocytosis [ 23 ]. These glutamate-independent modulatory effects of co-agonists are specific to certain types of neurons [ 27 ] and NMDAR subtypes [ 22 ], which may be associated with their ability to reduce the abuse liability of ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…The other possibility is the linking of glycine-receptor antibodies instead of glycine to binding sites on N-methyl-D-aspartate receptors. Glycine binding to NMDAR might result in NMDAR internalization (20). Thus, the linking of glycine-receptor autoantibodies to glycinebinding sites on NMDAR might result in internalizing NMDAR, thus disrupting excitatory synaptic transmission within the hippocampus to cause memory impairment.…”
Section: Discussionmentioning
confidence: 99%